Game On! Teaching English with Fun and Creativity: Gamification Implementation in Remote Rural Areas (Sukaraja Village, South Lampung) - Fini Widya Fransiska (Jurnal Pengabdian Masyarakat, 2024)
This research aims to explore the implementation of gamification in teaching English in remote rural areas, with a focus on Sukaraja Village, South Lampung. The aim of Community Service (PkM) activities is to increase students' interest and motivation in learning, overcome challenges in learning in remote areas, and foster creativity and critical thinking skills through a fun approach. Activity methods include selecting the implementation date and location, analyzing the field situation, introducing PkM activities through gamification design, and implementing appropriate English teaching methods. The results of PkM activities show a significant increase in students' English language understanding and skills, as well as positive perceptions of the use of gamification in learning.